Application of key performance indicators for maintenance management of clinics facilities - Shohet, Igal M.; Nobili, Lorenzo (International Journal of Strategic Property Management, 2017)
The investment in the development of the existing portfolio of clinics, as well as in their maintenance and operation, constitutes 3–4% of the annual budgets of health maintenance organizations (HMOs) in Israel. These clinics are the primary facilities for the provision of health services. The research objective was the implementation of previously defined key performance indicators (KPIs) in a 42 clinic sample in order to: (1) assess the maintenance performance of the facilities, (2) intraand inter-benchmark the performance and efficiency, (3) establish a policy for the strategic and tactical maintenance management, and (4) set priorities in the maintenance plan. These actions should be part of a cycle for continuous improvement of the performance and maintenance of the facilities. This set of seven hybrid KPIs can be used for the leading and lagging analysis of the planning and control of facility maintenance. A case study is presented as an example of the applicability of the method.